ASSESSMENT OF KARAMUSTAFA GOLD-BEARING Zn-Pb MINE (GÜMÜŞHANE, TÜRKİYE) AREA IN TERMS OF NATURAL AND ARTIFICIAL RADIOACTIVITY: ASSESSMENT OF KARAMUSTAFA MINE (GÜMÜŞHANE, TÜRKİYE) AREA IN TERMS OF NATURAL AND ARTIFICIAL RADIOACTIVITY - VURAL, Alaaddin; KAYA, Ali (Göbeklitepe Medical Science Journal, 2024)
This study aimed to assess the environmental effects of natural and artificial radioactivity contents, especially in the context of medical geology of base metal-containing mineral deposits. In the study, natural (226Ra, 232Th and 40K) and artificial (137Cs) radioactivity concentrations in the soil of the Karamustafa gold-bearing Zn-Pb-(±Cu) mining area, one of the important mines of Gümüşhane (NE Türkiye), were investigated. In order to determine the natural and artificial radioactivity of the mining area, 9 soil samples were collected from different parts of the field, taking into account the geological and alteration characteristics of the field. Samples prepared according to relevant laboratory procedures were analyzed for 232Th, 226Ra and 40K elements with a Poptop Ortec detector, and artificial radioactivity values of 137Cs were also measured. The 232Th values of the Karamustafa gold-bearing Zn-Pb-(±Cu) mine area vary between 13±0.86 and 72±1.49 Bq/kg, the 226Ra values vary between 13±0.38 and 56±1.54 Bq/kg, and. 40K values vary between 397±1.73 and 722.43±2.38 Bq/kg. It was determined that 137Cs values also vary between 0 and 6±0.03Bq/kg. When compared to the weighted world average of natural radio activity concentrations, it was determined that the average values of 40K and 226Ra activities were above the world average in almost all samples, and the 232Th values were above the world average in some samples. It has been determined that the artificial/human-derived 137Cs radioisotope values in the field are remarkably high. Considering the major radio indices calculated for the field, it was determined that the threshold values were exceeded in terms of absorbed dose rate and annual effective dose rate. When all the data obtained were evaluated together, it was concluded that it would be useful to study the field in detail in terms of natural and artificial radiation risk.